2014
DOI: 10.1016/j.neo.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p70 S6 Kinase (S6K1) Activity by A77 1726 and Its Effect on Cell Proliferation and Cell Cycle Progress

Abstract: Leflunomide is a novel immunomodulatory drug prescribed for treating rheumatoid arthritis. It inhibits the activity of protein tyrosine kinases and dihydroorotate dehydrogenase, a rate-limiting enzyme in the pyrimidine nucleotide synthesis pathway. Here, we report that A77 1726, the active metabolite of leflunomide, inhibited the phosphorylation of ribosomal protein S6 and two other substrates of S6K1, insulin receptor substrate-1 and carbamoyl phosphate synthetase 2, in an A375 melanoma cell line. A77 1726 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…Our recent study showed that A77 1726 induces the feedback activation of the PI-3 and MAP kinase pathways; and that PLX4720, an inhibitor of Raf kinase, and U0126, a MEK inhibitor, block A77 1726-induced phosphorylation of ERK1/2 T202/Y204 and MEK1/2 S217/S221 [32]. Here we found that these inhibitors did not change the levels of LC3-II lipidation in the presence of A77 1726 (Figure 3E).…”
Section: Resultssupporting
confidence: 50%
“…Our recent study showed that A77 1726 induces the feedback activation of the PI-3 and MAP kinase pathways; and that PLX4720, an inhibitor of Raf kinase, and U0126, a MEK inhibitor, block A77 1726-induced phosphorylation of ERK1/2 T202/Y204 and MEK1/2 S217/S221 [32]. Here we found that these inhibitors did not change the levels of LC3-II lipidation in the presence of A77 1726 (Figure 3E).…”
Section: Resultssupporting
confidence: 50%
“…Thus these drugs also inhibit the proliferation of EBV-transformed B cells through “off-target” mechanisms. Although the precise mechanism(s) for these off-target effects on EBV-transformed B cells remain to be determined, they likely reflect the previously described ability of higher dose leflunomide/teriflunomide treatment to inhibit multiple different cellular tyrosine kinases, as well as AKT, S6 Kinase, NF-KB and STAT3 signaling [ 16 , 23 , 52 ]. Interestingly, however, we found increased, rather than decreased, NF-kappa B signaling in teriflunomide treated LCLs, presumably due to the increased expression of LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Since cancerous cells need more nutrient substance to produce new cells, metabolic signaling pathways are suggested to be essential during carcinogenesis [ 33 ]. As a rate-limiting enzyme of nucleotide metabolism pathway, DHODH seemed to contribute to malignant characteristics of various tumors, including multiple myeloma [ 16 ], chronic lymphocytic leukemia [ 34 37 ], neuroblastoma [ 38 ], colon cancer [ 9 ], prostate cancer [ 39 ], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, DHODH inhibition by leflunomide induced a significant decrease in melanoma growth both in vitro and in vivo studies [ 18 ]. Several other studies also showed that teriflunomide could suppress growth of melanoma cells [ 16 , 19 ]. However, the mechanisms underlying remained to be further explored.…”
Section: Introductionmentioning
confidence: 95%